First-principles study on structural, elasto-mechanical, electronic, thermodynamic and hydrogen storage properties of XGeH3 (X=K, Rb) hydrides - Muhammad Salman Kiani; Abu Bakar; Erum Rehman (Results in Physics, 2025)
The first principles calculations are performed to calculate the structural, elastic, mechanical, phonon, electronic, optical, thermodynamic and hydrogen storage properties of lead free hydrides XGeH3(X = K,Rb). The structural parameters such as bulk modulus, volume and pressure derivative are calculated using optimized lattice constants. KGeH3 and RbGeH3 have the lattice constant of 7.686 (a.u.) and 7.853 (a.u.). The slight increase in the lattice constant of RbGeH3 is due to its larger ionic radii. The gravimetric hydrogen storage capacity Cwt% for KGeH3 and RbGeH3 is 2.58% and 1.84%. The electronic band structures and density of states suggested the metallic nature of both materials. The calculations of Pugh’s ratio, Poisson’s ratio and Cauchy pressure elucidated the brittle nature of XGeH3(X = K,Rb). The quasi harmonic approximation is employed to study thermodynamic properties. The entropy and volume increase with temperature, while Debye temperature decreases as the applied temperature increases. The current study indicates that lead free hydride hydrides XGeH3(X = K,Rb) are potential candidates for hydrogen storage applications.